"AN ATTEMPT TO A KINYANKORE CLASSIFICATION OF MUSICAL INSTRUMENTS”, by Paul van Thiel, W.F., Review of Ethnology, No. 13, 1969, pp. 1-5, Institut fur Volkerkunde, Vienna University. - Tracey, Andrew (International Library of African Music, 1970)
pages: 126
Keywords: African Music